Freedom to Learn from Ki Hadjar Dewantara's Perspective and its Relevance for the Development of Character Education - Jamil, Jumrah; M.Dun, Alyyuddin; Sahrun, Sahrun; Marhali, Rohani Dg; Joni, Juliati (Formosa Journal of Applied Sciences, 2023)
The aim of this research is to investigate and assess policy formulation. The concept of "freedom of learning" as presented by Ki Hadjar Dewantara and is relevant to the development of character education, gives educators and students the freedom to choose the type of learning environment they want. Because the world of education in Indonesia currently places more emphasis on knowledge than skills, the aim of freedom to learn is to make learning fun for teachers and students. In addition, character development is highly valued at Merdeka Belajar. in line with Indonesian national values. According to Hadjar Dewantara Ki, learning is a catalyst for student growth because it teaches them how to make changes and improve the environment. One way to practice the values that shape the character of a country is to give people the freedom to learn, starting with improving the education system and teaching strategies.